تأثير نوعية العلف على نمو اصبعيات المشط الأزرق (Oreochromis aureus) المرباة في المياه شبه المالحة (Latakia University Journal -Biological Sciences Series, 2019)
This study has been conducted to investigate the effect of different diet qualities on growth performance and feed conversion of Oreochromis aureus fingerlings reared in brackish water (salinity, 20‰) of 100 liters glass aquaria. The fingerlings were fed two diet types which differ by their dietary protein and lipid contents: a scientific diet (SD) and a commercial diet (CD), twice a day to satiation for 30 days. The results revealed that the best growth rates (ADG, % weight gain, SGR) were significantly higher (P